P85 Do gender-based disparities in authorship and editorialship exist in healthcare simulation journals? a bibliometric review of the research. (3rd November 2019) - Lydon, Sinéad; Bhulbh, Áine De; Maher, Senan; Madden, Caoimhe; Byrne, Dara; O'Connor, Paul
Abstract : Background: Although academic publishing is intended to be objective, and thus should be gender neutral, a gender bias in the authorship of papers has been observed across varied medical specialties. 1 Similarly, research suggests that women are underrepresented on editorial boards of influential medical journals. 2 The purpose of this study was to carry out a retrospective bibliometric review to assess whether gender-based disparities in authorship and editorialship exists across three healthcare simulation journals. Summary of work: All articles published in the three existing healthcare simulation-specific journals (i.e., Simulation in Healthcare, BMJ Simulation and Technology Enhanced Learning, and BMC Advances in Simulation) were examined from the first published issue of each journal until the final issue of 2018. Data extracted related to authorship of papers published in each of the three journals (i.e., type of article; gender of first and last authors; country and affiliation of first and last authors) and editorialship at each journal (i.e., the gender of each member of the journal's editorial board). Summary of results: A total of 873 studies (49.5% original research, 50.5% non-research) met the inclusion criteria. Table 1 presents the gender comparison of first and last authors, and editorial board members for each journal. First and last authors were predominantly male across all journals. Further, with the exception of a female Editor-in-Chief of one journal, and a greater proportion of female than male associate editors in another, gender disparities across the remaining categories of editorial boards existed. Discussion and conclusions: Male overrepresentation in authorship and editorialship was evident across the included journals, with female representation rates similar to those of previously conducted studies across a range of medical fields such as psychiatry, surgery and paediatrics. Recommendations: Considering publication in peer-reviewed journals, and serving on editorial boards, is considered an important indicator of academic productivity and success, and serves as a means of influencing discourse and practice in a field, future efforts should focus on actionable strategies to improve rates of female authorship and editorialship. References: Mueller C, Wright R, Girod S. The publication gender gap in US academic surgery. BMC surgery . 2017;17(1):16. Jagsi R, Tarbell NJ, Henault LE, Chang Y, Hylek EM. The Representation of Women on the Editorial Boards of Major Medical Journals: A 35-Year Perspective. Arch Intern Med . 2008;168(5):544–548.